Type A Behavior, Emotional Intelligence and Social Self-Efficacy as Predictors of Work Motivation among Faculty Members at the Hashemite University - Ghaleb AL-Baddareen; Souad Ghaith; Mutasem Akour; Suhaila Banat (Sultan Qaboos University, 2012)
This study examined the association between type A behavior, emotional intelligence, social self-efficacy, and work motivation among faculty members at the Hashemite University in Jordan. Seventy seven faculty members responded to four measures: Type A behavior scale, emotional intelligence scale, perceived social self-efficacy scale, and work motivation scale. The results of this study revealed that emotional intelligence was positively and significantly related to work motivation. Moreover, this study confirmed the value of emotional intelligence as a significant predictor of work motivation. However, social-self-efficacy and Type A behavior proved to be non significant predictors of work motivation